Pusa sibirica - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
17. Baikal Seal Pusa sibirica French: Phoque du Baikal / German: Baikal-Ringelrobbe / Spanish: Foca del Baikal Other common names: Lake Baikal Seal, Nerpa Taxonomy. Phoca sibirica Gmelin, 1788, “Baikal et Orom” (= Lake Baikal and Lake Oron, Russia). This species is monotypic. Distribution. lake Baikal in S Siberia, Russia. Descriptive notes. Total length 130-145 cm (males) and 120-130 cm (females); weight 50-90 kg. Newborns are 60-65 cm in length and weigh c.4 kg. Baikal Seals are unspotted, or occasionally very sparsely and faintly spotted, with small heads and robust bodies. Claws on front flippers are relatively long, thick, and strong—evidently adaptations for living under the ice for much of autumn through spring when Lake Baikal freezes over and for helping them to get traction on the ice surface at pressure cracks and small breathing holes that they keep open. Offspring are born with a white lanugo (fine, soft hair) that is shed at 4-6 weeks old and replaced by shorter silver gray hair. Adult Baikal Seals are silver-gray to brown dorsally and yellowish white ventrally. Habitat. Confined to freshwater Lake Baikal where they have been isolated from their Arctic marine ancestors for several hundred thousand years. Baikal Seals haul-out on island shorelines in summer but otherwise live on or under the lake’s frozen surface from autumn through spring. Food and Feeding. Baikal Seals eat a large diversity offish, although the golomyankas or Baikal oilfish (Comephorus spp.) and Baikal sculpins (Cottocomephorus spp.) are their most important prey. Baikal Seals occasionally eat omul (Coregonus migratorius), a commercially harvested fish, in summer. Prey is captured mostly at depths of 10-50 m at night and 100-200 m during the day. In aquaria, Baikal Seals have been recorded to consume c.4-6% oftheir body weight/day, or ¢.5-6 kg offish. Breeding. Mating of Baikal Seals occurs in water in late spring, just after offspring are weaned. Little is known about breeding structure of Baikal Seals, although they seem to be ...